(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present paper is based on Ayurvedic concept “Causes of Manasvikar.” Here we can see the causative factors of Manasvikar. Basically those people having stressful lifestyle with Insomnia, Depression, oc.disorder‘s, hallucinations, Dis- hallucinations, Epilepsy, schizophrenia disorder, High great fever, Alcoholism, Hypertension, thyroid problems, Obesity, as Will as auto – immune Diseases found Anger as a symptoms Hence Acharya Charaka also explain about srotas & their vitiation due to vatadi doshas & Raj with Tam give primary information of Anger & their effect on body. Anger usually increased due to Raj vardhan that repeated to Pitta Hence it vitiated also Rakta which indicates so many disease due to Impurification of blood. In today‘s changing world while the poor are not risk to afford good diet & the rich due to their fond-ness for junk food do not eat a balanced diet. On that Anger (Krodha) is mentioned as a mental factor in dharniya vegas. Finally main intention for presenting this paper is to share basic details of Causes of Manasvikar as proper Treatment.